Study on the Causes of Inaccuracy of Qibla Direction of the Great Mosque Baitul Makmur West Aceh - Riza Afrian Mustaqim; Reza Akbar (Jurnal Ilmiah Al-Syir'ah, 2021)
The accuracy of the Qibla direction at the Baitul Makmur Great Mosque in West Aceh cannot tolerate. The reason is that the value of deviation is so high that it does not face ainul ka'bah or even jihatul ka'bah. This Qiblah direction is not by the minimum limit of tolerance for the variation of the Qibla direction and is not by the Islamic legal status. This study examines the causes of the inaccuracy of the Qibla of the Great Mosque of Baitul Makmur Meulaboh West Aceh, namely the lack of role of figures and efforts to maintain the architecture of the mosque building. This research belongs to qualitative field research, by verifying the direction of the Qiblah with the rashdul qibla method and google earth observation to explore causes of inaccuracy. Interview techniques are also used to obtain in-depth field data. The analysis technique used is descriptive analysis. This study indicates that the inaccuracy of the Qibla direction of the Baitul Makmur Great Mosque in West Aceh is inseparable from the minor role of religious figures and leaders at the beginning of the Mosque's construction. Until now, the direction of the Mosque's Qiblah is still parallel to the mihrab. Renovations were also not carried out because of maintaining the architecture of the mosque building. Renovation of the mosque building to calibrate the Qibla direction would reduce the aesthetics of the mosque building.